Study on Sound Wave Scattering Effects of Different Markers Placed on Dam Face in Deepwater Reservoir - Yan Xiang; GuangZe Shen; ZhengFei Cheng; Kai Zhang (Advances in Civil Engineering)
Reservoir dams are mostly built in alpine valley areas. The water surface of the river valley is narrow and the geometric features of hydraulic structures are complex, which result in different absorption, reflection, and diffraction effects on sound waves for various propagation media. Further, for relatively narrow underwater water space where the underwater detection equipment is located, there is significant interference to the underwater acoustic communication signal. This is a major challenge to underwater positioning technology. Therefore, in this study, the scattering effect of different markers placed on a dam face on the sound waves emitted by sonar carried by a remote control unmanned submersible in a reservoir environment was investigated. The singular boundary method was used to develop a simulation model of the scattering effect on the sound waves of three different markers (i.e., cross boards, spherical bodies, and square plates) placed on a dam face in the deepwater environment of a reservoir. The scattering effect of typical geometrical markers was also investigated with respect to the sound waves of different frequencies and different incident angles. The sound pressure level (SPL) was used as an indicator for determining the scattering effect, so that the geometry of the marker with well scattering effect could be determined. In this study, the Guanyinyan hydropower dam was considered as the research area. The results show that the scattering SPL of the cross board is higher than those of the spherical body and the square plate, i.e., using the cross board as a marker produces the most accurate positioning of the underwater detection remote control unmanned submersible of a dam project in the deepwater environment of a reservoir.